On the family- and genus-series nomina in Gyrinidae Latreille, 1810 (Coleoptera, Adephaga) - Gustafson, Grey T.; Miller, Kelly B. (Zootaxa, 2013)
All available genus- and family- group nomina for the Gyrinidae (Coleoptera: Adephaga) are listed along with original citation, original and current status, type nominal taxon with method of designation, and known synonymies and incorrect subsequent spellings. The nomina included follow the most current classification. Discussion is provided clarifying numerous nomenclatural problems with original spellings, correct authorship and type designation. Dineutini Ochs, 1926 syn. nov. is found to be a junior homonym of Dineutini Desmarest, 1851, and Enhydrini Régimbart, 1882 syn. nov. and its justified emendation Enhydrusini (Anonymous 2012) are here synonymized with Dineutini Desmarest, 1851.